Composite membrane, membrane-electrode assembly, solid polymer fuel cell, solid polymer electrolysis device, and electrochemical hydrogen compression device

The composite membrane, featuring a polyolefin microporous membrane, silica material with sulfonic acid groups, and ion exchange resin, addresses the challenges of proton conductivity and dimensional stability in solid polymer fuel cells and electrolytic devices, achieving efficient energy conversion and storage.

JP2025050176APending Publication Date: 2025-04-04TEIJIN LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023158829
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing electrolyte membranes in solid polymer fuel cells and electrolytic devices face challenges in achieving both high proton conductivity and dimensional stability, which are crucial for efficient energy conversion and storage.

Method used

A composite membrane is developed, comprising a porous substrate made of polyolefin microporous membrane, a silica material with sulfonic acid groups, and an ion exchange resin. The composite membrane has a Galley value of 1,000 seconds/100 mL or more, with a porosity of 50% to 90% and a specific structure that enhances proton conductivity and dimensional stability.

Benefits of technology

The composite membrane exhibits excellent proton conductivity and dimensional stability, making it suitable for use in solid polymer fuel cells, electrolytic devices, and electrochemical hydrogen compression devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025050176000005
    Figure 2025050176000005
  • Figure 2025050176000006
    Figure 2025050176000006
  • Figure 2025050176000001
    Figure 2025050176000001
Patent Text Reader

Abstract

To provide a composite membrane having excellent proton conductivity and dimensional stability.SOLUTION: A composite membrane includes a porous substrate including a polyolefin microporous membrane, a silica material having a substrate including silicon dioxide, and sulfonic acid groups on at least the surface of the substrate, and an ion exchange resin, and has a Gurley value of 1,000 seconds / 100 mL or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a composite membrane, a membrane-electrode assembly, a polymer electrolyte fuel cell, a polymer electrolyte electrolysis device, and an electrochemical hydrogen compression device. [Background technology]

[0002] In recent years, there is an increasing need to improve the performance of electrolyte membranes, especially solid polymer electrolyte membranes. For example, a system that generates hydrogen by electrolyzing water using renewable energy such as solar or wind power, compresses the generated hydrogen, stores it at high density, and supplies the hydrogen to a fuel cell at a place where electricity is needed when it is needed, has attracted attention as a very clean energy system that does not generate carbon dioxide. Here, a water electrolysis method is known in which the anode and cathode are separated by an electrolyte membrane, protons generated at the anode are transferred to the cathode through the electrolyte membrane, and hydrogen is obtained by combining with electrons at the cathode. The reaction formula at each electrode is as follows. ·Anode: H2O→1 / 2O2+2H + +2e - ·Cathode: 2H + +2e - →H2 On the other hand, in a fuel cell, protons produced in the hydrogen oxidation reaction at the negative electrode (anode) move through the electrolyte membrane to the positive electrode (cathode), where they generate water through an oxygen reduction reaction, generating electricity. The reaction formula at each electrode is as follows: ·Negative electrode: H2→2H + +2e - ·Positive electrode: 1 / 2O2+2H + +2e - →H2O

[0003] As is clear from the above operating principles, improving the proton conductivity of the electrolyte membrane is a common issue in both water electrolysis and fuel cells. Possible methods for improving the proton conductivity of the electrolyte membrane include reducing the membrane thickness and reducing the dry mass per equivalent of ion exchange groups in the electrolyte polymer (equivalent weight: EW). However, there is a natural limit to how thin the electrolyte membrane can be made, given the strength required for the membrane between the electrodes. In addition, reducing the EW can also lead to a decrease in the ratio of the electrolyte polymer skeleton, making it difficult to maintain a solid membrane.

[0004] In order to ensure the strength of the electrolyte membrane, there is an example where a polymer electrolyte is contained in the internal space (void) of a polymer porous membrane as a polymer electrolyte for a fuel cell, thereby achieving an improvement in mechanical strength that could not be achieved by the electrolyte itself (Patent Document 1). Also, a porous substrate suitable for holding a polymer electrolyte in a polyethylene porous membrane has been proposed (Patent Document 2). Furthermore, there is a conventional technology in which a thin electrolyte film with excellent mechanical strength is provided by incorporating and containing an ion exchange resin in the network structure of a porous thin film of ultra-high molecular weight polyolefin (Patent Document 3). There is also a conventional technology in which a thin electrolyte film with excellent mechanical strength is provided by incorporating and containing an ion conductor in a solid polymer porous membrane by utilizing the capillary condensation effect (Patent Document 4). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-166557 A [Patent Document 2] JP 2011-241361 A [Patent Document 3] Japanese Unexamined Patent Publication No. 64-22932 [Patent Document 4] Japanese Patent Application Publication No. 1-158051 Summary of the Invention [Problem to be solved by the invention]

[0006] Although the above-mentioned methods have been studied to improve the proton conductivity of the electrolyte membrane, further improvement in the proton conductivity of the electrolyte membrane is required. On the other hand, when the electrolyte membrane is mounted in a device such as a fuel cell, the dimensional stability of the electrolyte membrane is also an important characteristic. Thus, the development of an electrolyte membrane that exhibits excellent proton conductivity and excellent dimensional stability is awaited. The present disclosure has been made in consideration of the above-mentioned conventional circumstances, and has an object to provide a composite membrane excellent in proton conductivity and dimensional stability, as well as a membrane-electrode assembly, a solid polymer electrolyte fuel cell, a solid polymer electrolysis device, and an electrochemical hydrogen compression device that use the composite membrane. [Means for solving the problem]

[0007] Specific means for achieving the above object are as follows. <1> A porous substrate comprising a polyolefin microporous membrane; A silica material having a substrate containing silicon dioxide and having sulfonic acid groups on at least a surface of the substrate; An ion exchange resin, A composite membrane with a Gurley value of 1,000 seconds / 100 mL or more. <2> The porosity of the porous substrate is 50% to 90%. <1> The composite membrane according to claim 1. <3> At least a portion of the pores of the porous substrate is filled with the silica material and the ion exchange resin. <1> or <2> The composite membrane according to claim 1. <4> The porous substrate and an ion-conducting layer including the silica material and the ion exchange resin provided on at least one surface side of the porous substrate. <1> ~ <3> 13. The composite membrane according to claim 12 . <5> The ratio (A / B) of the average thickness A of the porous substrate to the average thickness B of the composite membrane is 0.10 to 1.0. <1> ~ <4> 13. The composite membrane according to claim 12 . <6> The ratio (C / D) of the basis weight C of the porous substrate to the basis weight D of the composite membrane is 0.03 to 0.5. <1> ~ <5> 13. The composite membrane according to claim 12 . <7> The ratio of the concentration of sulfur atoms to the total concentration of silicon atoms and sulfur atoms of the silica material, as determined by X-ray fluorescence spectrometry (XRF), is 0.01% to 90%. <1> ~ <6> 13. The composite membrane according to claim 12 . <8> The substrate is in the form of particles. <1> ~ <7> 13. The composite membrane according to claim 12 . <9> The substrate is made of silica particles, and the number average particle size of the primary particles of the silica particles is 1 nm to 500 nm. <1> ~ <8> 13. The composite membrane according to claim 12 . <10> <1> ~ <9> 1. A membrane-electrode assembly comprising the composite membrane according to any one of claims 1 to 9, a cathode laminated on one surface of the composite membrane, and an anode laminated on the other surface of the composite membrane. <11> <10> and separators disposed on both sides of the membrane-electrode assembly. <12> <10> and separators disposed on both sides of the membrane-electrode assembly. <13> <1> ~ <9> 13. An electrochemical hydrogen compression device comprising the composite membrane according to claim 12. Effect of the Invention

[0008] According to the present disclosure, it is possible to provide a composite membrane having excellent proton conductivity and dimensional stability, as well as a membrane-electrode assembly, a solid polymer electrolyte fuel cell, a solid polymer electrolysis device, and an electrochemical hydrogen compression device that use this composite membrane. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 shows a cross-sectional view of one embodiment of a composite membrane of the present disclosure. [Diagram 2] 1 shows a cross-sectional view of another embodiment of a composite membrane of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present disclosure will be described in detail below. However, the present disclosure is not limited to the following embodiments. In the following embodiments, the components (including element steps, etc.) are not essential unless otherwise specified. The same applies to numerical values ​​and their ranges, and do not limit the present disclosure.

[0011] In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, each component may contain multiple types of corresponding substances. When multiple types of substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, the particles corresponding to each component may include multiple types of particles. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified. In the present disclosure, the terms "layer" and "film" include cases where the layer or film is formed over the entire area when the area in which the layer or film is present is observed, as well as cases where the layer or film is formed over only a portion of the area. In this disclosure, the term "lamination" refers to stacking layers, where two or more layers may be bonded together or two or more layers may be removable. In this disclosure, with respect to a porous substrate, "longitudinal direction" refers to the longitudinal direction of a porous substrate (polyolefin microporous membrane) manufactured in a lengthwise shape, and "width direction" refers to the direction perpendicular to the longitudinal direction of the porous substrate (polyolefin microporous membrane).

[0012] <Composite membrane> The composite membrane of the present disclosure has a porous substrate including a polyolefin microporous membrane, a substrate including silicon dioxide, a silica material having sulfonic acid groups on at least the surface of the substrate, and an ion exchange resin, and has a Gurley value of 1,000 seconds / 100 mL or more. The composite membrane of the present disclosure has the above-mentioned configuration and is therefore excellent in proton conductivity and dimensional stability. Although the reason why the composite membrane of the present disclosure can exhibit such an effect is unclear, the present inventors speculate as follows. However, the following speculation is not intended to limit the composite membrane of the present disclosure, but is merely an example. A porous substrate containing a microporous polyolefin membrane exhibits high mechanical strength, and therefore it is presumed that the composite membrane of the present disclosure contains a porous substrate containing a microporous polyolefin membrane, thereby imparting excellent dimensional stability to the composite membrane of the present disclosure. Moreover, the silica material has a sulfonic acid group at least on the surface of the substrate containing silicon dioxide, and therefore exhibits proton conductivity. Furthermore, the composite membrane of the present disclosure contains an ion exchange resin together with the silica material. Here, the ion exchange resin contains a sulfonic acid group, a carboxyl group, a quaternary ammonium group, or a primary, secondary or tertiary amino group as an ion exchange group. In particular, a sulfonic acid group is an example of a suitable ion exchange group contained in the ion exchange resin constituting the solid polymer electrolyte membrane. Since the silica material has a sulfonic acid group at least on the surface of the substrate containing silicon dioxide, it has a high affinity with the ion exchange group (particularly the sulfonic acid group). By dispersing the silica material in the ion exchange resin, the ion exchange group contained in the ion exchange resin and the sulfonic acid group contained in the silica material interact with each other in the composite membrane, and a proton conductive path is easily constructed efficiently in the composite membrane. Therefore, it is presumed that the composite membrane of the present disclosure exhibits excellent proton conductivity.

[0013] The porous substrate, silica material, and ion exchange resin constituting the composite membrane of the present disclosure, as well as other elements used as necessary, will be described below.

[0014] (Porous base material) The composite membrane of the present disclosure contains a porous substrate containing a polyolefin microporous membrane from the viewpoints of chemical stability, mechanical strength, and hydrophobicity. The porous substrate may be made of a polyolefin microporous membrane. In the present disclosure, a microporous membrane containing a polyolefin is referred to as a "polyolefin microporous membrane." In the present disclosure, a microporous membrane refers to a membrane having a structure in which a large number of micropores are present inside and the micropores are interconnected, allowing gas or liquid to pass from one surface to the other surface.

[0015] The microporous polyolefin membrane preferably has a three-dimensional network structure composed of polyolefin fibrils.

[0016] Examples of the polyolefin contained in the polyolefin microporous film include polyethylene, polypropylene, polybutylene, polymethylpentene, copolymers of polypropylene and polyethylene, etc. Among these, polyethylene is preferred, and high-density polyethylene, a mixture of high-density polyethylene and ultra-high molecular weight polyethylene, etc. are suitable.

[0017] An example of an embodiment of the polyolefin microporous membrane is a polyethylene microporous membrane containing only polyethylene as a polyolefin.

[0018] An example of an embodiment of a polyolefin microporous film is a microporous film containing polypropylene, which has heat resistance such that the film does not easily break when exposed to high temperatures.

[0019] An example of an embodiment of the microporous polyolefin membrane is a microporous polyolefin membrane that contains at least a mixture of polyethylene and polypropylene.

[0020] An example of an embodiment of the microporous polyolefin membrane is a microporous polyolefin membrane having a laminated structure of two or more layers, at least one of which contains polyethylene and at least one of which contains polypropylene.

[0021] The weight average molecular weight (Mw) of the polyolefin contained in the polyolefin microporous membrane is preferably 500,000 to 5,000,000. When the Mw of the polyolefin is 500,000 or more, the microporous membrane can be imparted with sufficient mechanical properties. When the Mw of the polyolefin is 5,000,000 or less, the microporous membrane can be easily formed.

[0022] The weight average molecular weight (Mw) of the polyethylene contained in the polyolefin microporous film is preferably 800,000 or more, more preferably 1,000,000 or more, and even more preferably 1,100,000 or more, from the viewpoint of densifying the porous structure of the microporous film. The weight average molecular weight (Mw) of the polyethylene contained in the polyolefin microporous membrane is preferably 4.9 million or less, more preferably 4.8 million or less, and even more preferably 4.7 million or less, from the viewpoint of increasing the porosity of the microporous membrane. When the microporous polyolefin film contains two or more types of polyethylene, the weight average molecular weight (Mw) of the mixture of two or more types of polyethylene is preferably within the above range.

[0023] The weight average molecular weight of the polyolefin and polyethylene constituting the microporous polyolefin membrane is obtained by dissolving the microporous polyolefin membrane in o-dichlorobenzene under heating, and measuring the molecular weight by gel permeation chromatography (system: Alliance GPC 2000 manufactured by Waters, columns: GMH6-HT and GMH6-HTL) at a column temperature of 135°C and a flow rate of 1.0 mL / min. Monodisperse polystyrene (manufactured by Tosoh Corporation) is used to calibrate the molecular weight.

[0024] An example of an embodiment of the polyolefin microporous membrane is a microporous membrane containing a polyolefin composition (which in the present disclosure means a mixture of polyolefins containing two or more kinds of polyolefins, and when the polyolefin contained is only polyethylene, it is called a polyethylene composition.) The polyolefin composition forms a network structure with fibrillation during stretching, and has the effect of increasing the porosity of the polyolefin microporous membrane.

[0025] The polyolefin composition has a weight average molecular weight of 9×10 5 The polyolefin composition preferably contains 5% by mass to 90% by mass of the above ultra-high molecular weight polyethylene, more preferably 10% by mass to 88% by mass, and even more preferably 15% by mass to 85% by mass, based on the total amount of polyolefins.

[0026] The polyolefin composition has a weight average molecular weight of 9×10 5 and ultra-high molecular weight polyethylene having a weight average molecular weight of 2×10 5 ~8×10 5 and density is 920kg / m 3 ~960kg / m 3 and a high-density polyethylene in a mass ratio of 5:95 to 95:5 (more preferably 10:90 to 90:10, and further preferably 15:85 to 85:15).

[0027] An example of the embodiment of the polyolefin microporous membrane is a polyolefin microporous membrane that has been hydrophilized. Examples of the polyolefin microporous membrane that has been hydrophilized include a polyolefin microporous membrane whose surface is coated with a hydrophilic compound (e.g., ethylene-vinyl alcohol copolymer); a polyolefin microporous membrane whose surface is polymerized with a monomer having a hydrophilic group; a polyolefin microporous membrane that has been subjected to plasma treatment or corona treatment; etc.

[0028] From the viewpoint of dimensional stability, the proportion of the porous substrate in the composite membrane of the present disclosure is preferably 5.0 mass % or more, more preferably 5.5 mass % or more, and even more preferably 6.0 mass % or more. From the viewpoint of proton conductivity, the proportion of the porous substrate in the composite membrane of the present disclosure is preferably 20 mass % or less, more preferably 18 mass % or less, and even more preferably 16 mass % or less. The proportion of the porous substrate in the composite membrane of the present disclosure is preferably 5.0 mass % to 20 mass %, more preferably 5.5 mass % to 18 mass %, and even more preferably 6.0 mass % to 16 mass %.

[0029] (Method of producing a polyolefin microporous membrane) The method for producing the microporous polyolefin membrane of the present disclosure is not particularly limited, and for example, a method including the following steps (1) to (5) is preferred. The polyolefin used as the raw material is as described above.

[0030] (1) Preparation of polyolefin solution A polyolefin solution is prepared by dissolving a polyolefin in a solvent. Examples of the solvent include paraffin, liquid paraffin, paraffin oil, mineral oil, castor oil, tetralin, ethylene glycol, glycerin, decalin, toluene, xylene, diethyltriamine, ethyldiamine, dimethylsulfoxide, and hexane. In this case, the solvent may be used alone or in combination of two or more kinds. Among the solvents, examples of volatile solvents include solvents having a boiling point of less than 300° C. under atmospheric pressure, such as decalin, toluene, xylene, diethyltriamine, ethyldiamine, dimethylsulfoxide, hexane, tetralin, ethylene glycol, glycerin, etc. Examples of non-volatile solvents include solvents having a boiling point of 300° C. or more under atmospheric pressure, such as paraffin, liquid paraffin, paraffin oil, mineral oil, castor oil, etc. Examples of mixed solvents include a combination of decalin and liquid paraffin. When liquid paraffin is used as a solvent, the average pore size of the polyolefin microporous membrane tends to be smaller. When decalin is used alone as a solvent, the average pore size of the polyolefin microporous membrane tends to be larger than when liquid paraffin is used in combination. However, the average pore size can also be controlled by other process parameters, and is not limited to this.

[0031] The polyolefin concentration of the polyolefin solution is preferably 1% by mass to 45% by mass, more preferably 10% by mass to 40% by mass. When the polyolefin concentration is 1% by mass or more, the gel composition obtained by cooling gelation can be maintained so as not to be highly swollen by the solvent, so that it is difficult to deform and has good handleability. On the other hand, when the polyolefin concentration is 45% by mass or less, the pressure during extrusion is suppressed, so that the discharge amount can be maintained, and productivity is excellent.

[0032] (2) Extrusion of polyolefin solution The prepared polyolefin solution is kneaded in a single-screw extruder or a twin-screw extruder, and extruded through a T-die, a cross-hanger die, or an I-die at a temperature of the melting point or higher and the melting point + 70° C. or lower. In this case, a twin-screw extruder is preferably used. The polyolefin solution extruded from the die is then passed through a chill roll or a cooling bath to form a gel composition. At this time, it is preferable to gel the polyolefin solution by rapidly cooling it to a temperature below its gelling temperature.

[0033] (3) Solvent removal treatment Next, the solvent is removed from the gel composition. When a volatile solvent is used in the preparation of the polyolefin solution, the solvent can be removed from the gel composition by evaporating it by heating or the like, which also serves as a preheating step. When a non-volatile solvent is used in the preparation of the polyolefin solution, the solvent can be removed by squeezing it out under pressure or the like. It is not necessary to completely remove the solvent.

[0034] (4) Stretching of gel composition Following the solvent removal treatment, the gel composition is stretched. Here, a relaxation treatment may be performed before the stretching treatment. In the stretching treatment, the gel composition is heated and uniaxially or biaxially stretched at a predetermined magnification by a normal tenter method, roll method, rolling method, or a combination of these methods. The biaxial stretching may be either simultaneous or sequential. Also, it may be a longitudinal multi-stage stretching or a 3- or 4-stage stretching. The stretching temperature is preferably 80° C. or higher and lower than the melting point of the polyolefin used in the production, more preferably 90° C. to 130° C. If the heating temperature is lower than the melting point, the gel composition is less likely to dissolve, and stretching can be performed well. If the heating temperature is 80° C. or higher, the gel composition is sufficiently softened, and high-magnification stretching is possible without film rupture during stretching. The stretching ratio varies depending on the thickness of the raw film, but is preferably at least 2 times, more preferably 4 to 20 times in one axial direction. After stretching, heat setting is carried out as necessary to impart thermal dimensional stability.

[0035] (5) Extraction and removal of solvent The stretched gel composition is immersed in an extraction solvent to extract the solvent, particularly the non-volatile solvent. The extraction solvent may be, for example, a volatile solvent such as pentane, hexane, heptane, cyclohexane, decalin, or tetralin, a chlorinated hydrocarbon such as methylene chloride, carbon tetrachloride, or methylene chloride, a fluorinated hydrocarbon such as trifluoroethane, or an ether such as diethyl ether or dioxane. These solvents may be appropriately selected according to the solvent, particularly the non-volatile solvent, used in the preparation of the polyolefin solution, and may be used alone or in combination. The solvent extraction is performed by removing the solvent in the polyolefin microporous membrane to less than 1% by mass.

[0036] (Physical properties of porous substrate) From the viewpoint of increasing the strength of the porous substrate, the average film thickness of the porous substrate is preferably 0.01 μm or more, more preferably 3 μm or more, even more preferably 3.5 μm or more, particularly preferably 4 μm or more, and most particularly preferably 5 μm or more. From the viewpoint of maintaining ion conductivity, the average film thickness of the porous substrate is preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, particularly preferably 100 μm or less, and even more particularly preferably 50 μm or less. The average film thickness of the porous substrate is preferably from 0.01 μm to 300 μm, more preferably from 3 μm to 250 μm, even more preferably from 3.5 μm to 200 μm, particularly preferably from 4 μm to 100 μm, and even more preferably from 5 to 50 μm. The average film thickness of the porous substrate is determined by measuring 20 points with a contact type film thickness meter and averaging the results.

[0037] The porosity of the porous substrate is preferably 50% or more, more preferably 51% or more, even more preferably 52% or more, and particularly preferably 53% or more, from the viewpoint of the filling rate of the silica material and the ion exchange resin. The porosity of the porous substrate is preferably 90% or less, more preferably 88% or less, even more preferably 85% or less, and particularly preferably 84% or less, from the viewpoint of the mechanical strength of the membrane. The porosity of the porous substrate is preferably from 50% to 90%, more preferably from 51% to 88%, further preferably from 52% to 85%, and particularly preferably from 53% to 84%.

[0038] The porosity of the porous substrate is determined by the basis weight (Ws: g / m 2 ), true density of polyolefin (ds: g / cm 3 ) and the membrane thickness (t: μm) of the porous substrate, the true density was calculated from the following formula. When the porous substrate contains two or more types of polyolefins, the true density of the polyolefin means the true density of a mixture of two or more types of polyolefins. ε(%)={1-Ws / (ds·t)}×100

[0039] From the viewpoint of mechanical strength, the Gurley value of the porous substrate is preferably 0.1 sec / 100 mL or more, more preferably 0.2 sec / 100 mL or more, even more preferably 0.5 sec / 100 mL or more, and particularly preferably 1 sec / 100 mL or more. From the viewpoint of maintaining ion conductivity, the Gurley value of the porous substrate is preferably 500 sec / 100 mL or less, more preferably 450 sec / 100 mL or less, further preferably 400 sec / 100 mL or less, and particularly preferably 300 sec / 100 mL or less. The Gurley value of the porous substrate is preferably 0.1 sec / 100 mL to 500 sec / 100 mL, more preferably 0.2 sec / 100 mL to 450 sec / 100 mL, further preferably 0.5 sec / 100 mL to 400 sec / 100 mL, and particularly preferably 1 sec / 100 mL to 300 sec / 100 mL. The Gurley value of the porous substrate is a value measured in accordance with JIS P8117:2009.

[0040] From the viewpoint of mechanical strength, etc., the breaking strength of the porous substrate is preferably 50 MPa to 400 MPa, and more preferably 80 MPa to 300 MPa.

[0041] The breaking strength is measured using a tensile tester in accordance with JIS L1015:2010. In the measurement of breaking strength, the chuck distance is 100 mm and the tensile speed is 50 mm / min. The tensile tester may be an EZ-LX manufactured by Shimadzu Corporation or a device of equivalent quality.

[0042] The average pore size of the porous substrate is preferably 0.001 μm or more, more preferably 0.005 μm or more, even more preferably 0.01 μm or more, and particularly preferably 0.02 μm or more, from the viewpoint of the filling ability of the silica material and the ion exchange resin. From the viewpoint of mechanical strength etc., the average pore size of the porous substrate is preferably 100 μm or less, more preferably 3.0 μm or less, even more preferably 2.0 μm or less, and particularly preferably 1.0 μm or less. The average pore size of the porous substrate is preferably from 0.001 μm to 100 μm, more preferably from 0.005 μm to 3.0 μm, further preferably from 0.01 μm to 2.0 μm, and particularly preferably from 0.02 μm to 1.0 μm. The average pore size of the porous substrate can be measured using a perm porometer in accordance with ASTM E1294-89. A fluorine-based inert liquid is used as the immersion liquid.

[0043] The basis weight of the porous substrate is set at 0.5 g / m2 from the viewpoint of mechanical strength. 2 More than 0.7 g / m is preferable. 2 More preferably, 1.0 g / m or more 2 More preferably, 1.5 g / m 2 The above is particularly preferred. The basis weight of the porous substrate is set to 50.0 g / m from the viewpoint of improving proton conductivity. 2 Less than 45.0 g / m is preferred. 2 Less than 40.0 g / m is more preferable. 2 More preferably, 20.0 g / m 2 The following are particularly preferred: The basis weight of the porous substrate is 0.5 g / m 2 ~50.0g / m 2 is preferred, and 0.7 g / m 2 ~45.0g / m 2 More preferably, 1.0 g / m 2 ~40.0g / m 2 More preferably, 1.5 g / m 2 ~20.0g / m 2 The following are particularly preferred: The basis weight of a porous substrate is determined by measuring the weight of a sample of a given size and dividing the weight by the area.

[0044] (Silica Materials) The composite membrane of the present disclosure has a substrate containing silicon dioxide and contains a silica material having sulfonic acid groups on at least the surface of the substrate, from the viewpoint of imparting proton conductivity to the composite membrane. The sulfonic acid groups may be chemically bonded to the surface of the substrate.

[0045] The silica material used in the present disclosure will now be described in detail.

[0046] -Base- The silica material has a substrate containing silicon dioxide. The shape of the substrate is not particularly limited, and examples thereof include a particulate, fibrous, plate-like, or thin-film substrate. From the viewpoint of the filling ability of the silica material into the pores of the porous substrate, the substrate is preferably particulate.

[0047] The particulate substrate containing silicon dioxide may be silica particles. The silica particles may be crystalline or amorphous. The silica particles may be particles produced from a silicon compound such as water glass or alkoxysilane as a raw material, or may be particles obtained by crushing quartz. Specific examples of the silica particles include silica particles produced by a sol-gel method, colloidal silica particles, fumed silica particles obtained by a gas phase method, and fused silica particles.

[0048] The number average particle size of the primary particles of the silica particles is preferably from 1 nm to 500 nm, more preferably from 5 nm to 300 nm, further preferably from 8 nm to 200 nm, and particularly preferably from 10 nm to 100 nm. The number-average particle size of the primary particles of the silica particles refers to a value calculated as the arithmetic mean value of the circle-equivalent diameters of 50 silica particles determined by observation with a scanning electron microscope. The primary particles of the silica particles may be aggregated to form secondary particles. The volume average particle size of the secondary particles of the silica particles is preferably from 500 nm to 500 μm, more preferably from 1 μm to 300 μm, and further preferably from 10 μm to 150 μm. The volume average particle size of the secondary particles of the silica particles is a value measured using a laser diffraction particle size distribution measuring device, for example, a Mastersizer 2000 manufactured by Sysmex Corp. Specifically, the volume average particle size is defined as the median particle size (D50) in the volume particle size distribution of a dispersion liquid in which silica particles, water (dispersion medium), and a nonionic surfactant (Igepal CA630; dispersant) are mixed and dispersed.

[0049] Examples of fibrous substrates containing silicon dioxide include glass fibers such as long glass fibers (glass fibers) and short glass fibers (glass wool), silica nanofibers, etc. The glass fibers are preferably made of non-alkali glass (E glass). The diameter of the glass fiber is not particularly limited, but is preferably 1 μm to 100 μm, and more preferably 5 μm to 50 μm. The fiber length of the long glass fibers is not particularly limited, and the fiber length of the short glass fibers is preferably 0.1 mm to 30 mm, and more preferably 0.2 mm to 20 mm. The diameter of glass fibers refers to the number-average fiber diameter, which indicates the average diameter of glass fibers. The number-average fiber diameter is the arithmetic average of the diameters of 50 randomly selected glass fibers measured under an optical microscope. The fiber length of the short glass fibers is a value obtained by visually measuring the length of 100 randomly selected fibers to the nearest 0.1 mm, and then calculating the arithmetic mean.

[0050] Examples of the thin film substrate containing silicon dioxide include flaky glass particles. The volume average particle diameter of the scaly glass particles is preferably 0.1 μm to 200 μm, more preferably 0.2 μm to 150 μm, and further preferably 0.2 μm to 100 μm. The volume average particle diameter of the scaly glass particles can be measured in the same manner as the volume average particle diameter of the silica particles. The average thickness of the scaly glass particles is preferably 1 μm to 20 μm, more preferably 1.5 μm to 15 μm, and even more preferably 2 μm to 10 μm. The average thickness of the scaly glass particles refers to the arithmetic mean of the thicknesses of 50 randomly selected glass particles out of 100 randomly selected glass particles, measured with an optical microscope. The ratio of the volume average particle diameter of the scaly glass particles to the average thickness (aspect ratio: volume average particle diameter / average thickness) is preferably from 1.2 to 2000, more preferably from 1.5 to 1500, and even more preferably from 2 to 1000. The aspect ratio of the scaly glass particles can be calculated as the ratio of the volume average particle diameter of the scaly glass particles to the average thickness determined by the above-mentioned method.

[0051] In addition to the above-mentioned thin film substrate, a plate-shaped substrate containing silicon dioxide may be used. Examples of the plate-shaped substrate include a glass plate. From the viewpoint of processability, the substrate is preferably silica particles or glass fibers, and more preferably silica particles.

[0052] -Sulfonic acid group- The silica material has sulfonic acid groups on at least the surface of the substrate, and the sulfonic acid groups may be chemically bonded to the surface of the substrate. The presence of sulfonic acid groups at least on the surface of the substrate can be confirmed, for example, by the following method. X-ray Photoelectron Spectroscopy (XPS), X-ray Fluorescence (XRF), etc. are used to confirm whether sulfur atoms are present in the silica material and to quantify the amount of sulfur atoms present. Scanning Electron Microscope-Energy Dispersive X-ray Spectrometry (SEM-EDX) is used to confirm whether sulfur atoms are present on the surface of the silica material. In addition, 0.1 g of the silica material is dispersed in 1.9 g of deionized water, and the pH of the dispersion (5 mass % dispersion) is measured at 25°C. If sulfur atoms are present on the surface of the silica material and the pH of the dispersion is 3 or less, it can be determined that at least the surface of the substrate has sulfonic acid groups.

[0053] In one embodiment, the ratio of sulfur atoms to silicon atoms (S / Si) contained in the silica material is preferably from 0.001 to 0.25, more preferably from 0.0015 to 0.2, and even more preferably from 0.002 to 0.15. In another embodiment, the ratio of sulfur atoms to silicon atoms (S / Si) contained in the silica material is preferably 0.001 to 0.72, more preferably 0.0015 to 0.67, and even more preferably 0.002 to 0.62. The amounts of sulfur atoms and silicon atoms contained in the silica material used in calculating the ratio of sulfur atoms to silicon atoms (S / Si) are the atomic abundances determined by XPS measurement.

[0054] In one embodiment, the concentration of sulfur atoms contained in the silica material is preferably 50 mg / kg to 250 g / kg, more preferably 150 mg / kg to 200 g / kg, and even more preferably 300 mg / kg to 150 g / kg. In another embodiment, the concentration of sulfur atoms contained in the silica material is preferably 50 mg / kg to 50 g / kg, more preferably 150 mg / kg to 30 g / kg, and even more preferably 300 mg / kg to 20 g / kg. The concentration of sulfur atoms contained in the silica material refers to the amount of atoms present determined by XRF measurement.

[0055] The sulfonation degree of the silica material (sulfonation degree based on XRF) is preferably 0.01% to 90%, more preferably 0.03% to 80%, and even more preferably 0.06% to 60%. The sulfonation degree based on XRF is a value calculated as a ratio of the concentration of sulfur atoms to the total concentration of silicon atoms and sulfur atoms calculated by XRF measurement.

[0056] In one embodiment, the proportion of the silica material in the composite membrane of the present disclosure is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, and even more preferably 0.8 mass % or more, from the viewpoint of ion conductivity. In one embodiment, the proportion of the silica material in the composite membrane of the present disclosure is preferably 20 mass % or less, more preferably 15 mass % or less, and even more preferably 10 mass % or less, from the viewpoint of dimensional stability. In one embodiment, the proportion of the silica material in the composite membrane of the present disclosure is preferably 0.1 mass % to 20 mass %, more preferably 0.5 mass % to 15 mass %, and even more preferably 0.8 mass % to 10 mass %. In another embodiment, the proportion of the silica material in the composite membrane of the present disclosure is preferably 0.5 mass % or more, more preferably 0.7 mass % or more, and even more preferably 0.8 mass % or more, from the viewpoint of ion conductivity. In another embodiment, the proportion of the silica material in the composite membrane of the present disclosure is preferably 45 mass % or less, more preferably 35 mass % or less, and even more preferably 25 mass % or less, from the viewpoint of dimensional stability. In another embodiment, the proportion of the silica material in the composite membrane of the present disclosure is preferably 0.5 mass % to 45 mass %, more preferably 0.7 mass % to 35 mass %, and even more preferably 0.8 mass % to 25 mass %.

[0057] -Method of manufacturing silica materials- The silica material has a sulfonic acid group at least on the surface of the substrate. The method for making the sulfonic acid group exist at least on the surface of the substrate is not particularly limited. For example, the silica material used in the present disclosure can be produced by contacting the above-mentioned substrate with a sulfonating agent. The method for contacting the substrate with the sulfonating agent is not particularly limited, and examples thereof include a method in which the substrate is immersed in the sulfonating agent, a method in which the substrate is sprayed with the sulfonating agent, and the like. The temperature of the sulfonating agent when it is brought into contact with the substrate is preferably 10°C to 90°C, more preferably 15°C to 80°C, and even more preferably 20°C to 70°C. The immersion time when the substrate is immersed in the sulfonating agent is preferably from 5 to 120 minutes, more preferably from 10 to 100 minutes, and further preferably from 15 to 60 minutes. When the substrate is immersed in the sulfonating agent, the ratio of the substrate to the sulfonating agent is preferably 1,000 to 50,000 parts by mass, more preferably 2,000 to 30,000 parts by mass, and even more preferably 3,000 to 20,000 parts by mass, per 100 parts by mass of the substrate. When the substrate is immersed in the sulfonating agent, a stirring treatment may be performed. The stirring method is not particularly limited, and examples thereof include stirring using a stirring blade and stirring using a stirring device having a planetary rotation mechanism. By using a stirring device having a planetary rotation mechanism, the presence of air bubbles can be efficiently removed. After contacting the substrate with the sulfonating agent, the substrate may be washed with ion-exchanged water, deionized water, or the like, and filtered, and if necessary, further washed with an organic solvent such as acetone and filtered, and the substrate may be dried to obtain a silica material.

[0058] Examples of the sulfonating agent include fuming sulfuric acid, concentrated sulfuric acid, dilute sulfuric acid, sulfuric anhydride, etc., with fuming sulfuric acid or concentrated sulfuric acid being preferred, and fuming sulfuric acid being more preferred. The concentration of sulfur trioxide in the fuming sulfuric acid is preferably 10% by mass to 80% by mass, more preferably 15% by mass to 75% by mass, and further preferably 20% by mass to 70% by mass.

[0059] (Ion exchange resin) The composite membrane of the present disclosure contains an ion exchange resin from the viewpoint of imparting proton conductivity to the composite membrane. The ion exchange group contained in the ion exchange resin is not particularly limited, and examples thereof include a sulfonic acid group, a carboxy group, a quaternary ammonium group, or a primary, secondary, or tertiary amino group. Among these, a sulfonic acid group is preferable because of its excellent proton conductivity.

[0060] The type of ion exchange resin contained in the composite membrane of the present disclosure is not particularly limited. Examples of the ion exchange resin include aromatic ion exchange resins and fluorine-based ion exchange resins.

[0061] Examples of aromatic ion exchange resins include sulfonated aromatic polymers such as polyphenylene, polyphenylene sulfide, polyphenylene oxide, diphenyl paraphenylene oxide, polysulfone, polyether sulfone, polyether ketone, polyether ether ketone, polyether ketone ketone, polyether nitrile, polyamide, polybenzazole, and polyimide. More specifically, sulfonated polyphenylene containing a structural unit represented by general formula (I), sulfonated polyphenylene sulfide containing a structural unit represented by general formula (II), sulfonated polyphenylene oxide containing a structural unit represented by general formula (III), sulfonated polydiphenyl paraphenylene oxide containing a structural unit represented by general formula (IV), sulfonated polysulfone containing a structural unit represented by general formula (V), sulfonated polyethersulfone containing a structural unit represented by general formula (VI), sulfonated polyethersulfone containing a structural unit represented by general formula (VII), sulfonated polyether ketones containing structural units represented by general formula (VIII), sulfonated polyether ether ketones containing structural units represented by general formula (IX), sulfonated polyether ketone ketones containing structural units represented by general formula (X), sulfonated polyether nitriles containing structural units represented by general formula (XI), sulfonated polybenzazoles containing structural units represented by general formula (XII), and sulfonated polyimides containing structural units represented by general formula (XIII). Among these, sulfonated polyethersulfone containing a structural unit represented by general formula (VI), sulfonated polyphenylene sulfide containing a structural unit represented by general formula (II), and sulfonated polysulfone containing a structural unit represented by general formula (V) are preferred, and sulfonated polyethersulfone containing a structural unit represented by general formula (VI) is more preferred. In the present disclosure, two or more kinds of ion exchange resins may be used in combination. When two or more kinds of ion exchange resins are used in combination, for example, a sulfonated polyethersulfone containing a structural unit represented by general formula (VI) may be used in combination with a sulfonated resin other than the above-mentioned polyethersulfone. In the general formulas (I) to (XIII), n represents an integer of 1 or 2 or more.

[0062] [ka]

[0063] [ka]

[0064] The sulfonation rate of the aromatic ion exchange resin is preferably from 5 mol % to 90 mol %, more preferably from 8 mol % to 80 mol %, and further preferably from 10 mol % to 70 mol %. In the present disclosure, the sulfonation ratio of an aromatic ion exchange resin refers to the proportion of structural units substituted with sulfonic acid groups in all structural units contained in the aromatic ion exchange resin.

[0065] Examples of fluorine-based ion exchange resins include perfluorosulfonic acid electrolyte polymers such as Nafion (registered trademark), Aciplex (registered trademark), Flemion (registered trademark), Aquivion, and Gore Select.

[0066] The EW of the ion exchange resin is preferably 200 or more, more preferably 250 or more, even more preferably 300 or more, and particularly preferably 350 or more. The EW is preferably 2600 or less, more preferably 2300 or less, even more preferably 2000 or less, and particularly preferably 1700 or less. When the EW is 2600 or less, the ionic conductivity of the composite membrane is further improved. When the EW is 200 or more, the dimensional stability of the composite membrane is further improved. The EW of the ion exchange resin is preferably 200 to 2600.

[0067] The EW of an acid-form ion exchange resin is measured by the following method. Approximately 0.02g to 0.10g of ion exchange resin is immersed in 50mL of 25°C saturated NaCl aqueous solution (0.26g / mL), and left for 10 minutes while stirring. Then, neutralization titration is performed using 0.01N aqueous sodium hydroxide solution (Fujifilm Wako Pure Chemical Industries, Ltd.) with phenolphthalein (Fujifilm Wako Pure Chemical Industries, Ltd.) as an indicator. The Na-type ion exchange membrane obtained after neutralization is rinsed with pure water, vacuum dried and weighed. The equivalent amount of sodium hydroxide required for neutralization is M (mmol), and the mass of the Na-type ion exchange membrane is W (mg), and the equivalent mass EW (g / eq) is calculated from the following formula. EW=(W / M)-22

[0068] In one embodiment, the proportion of the ion exchange resin in the composite membrane of the present disclosure is preferably 70.0 mass % or more, more preferably 75.0 mass % or more, and even more preferably 80 mass % or more, from the viewpoint of ion conductivity. In one embodiment, the proportion of the ion exchange resin in the composite membrane of the present disclosure is preferably 98.0 mass % or less, more preferably 95.0 mass % or less, and even more preferably 93.0 mass % or less, from the viewpoint of dimensional stability. In one embodiment, the proportion of the ion exchange resin in the composite membrane of the present disclosure is preferably 70.0 mass % to 98.0 mass %, more preferably 75.0 mass % to 95.0 mass %, and even more preferably 80.0 mass % to 93.0 mass %. In another embodiment, the proportion of the ion exchange resin in the composite membrane of the present disclosure is preferably 50 mass % or more, more preferably 60 mass % or more, and even more preferably 70 mass % or more, from the viewpoint of ion conductivity. In another embodiment, the proportion of the ion exchange resin in the composite membrane of the present disclosure is preferably 95 mass % or less, more preferably 94 mass % or less, and even more preferably 93 mass % or less, from the viewpoint of dimensional stability. In another embodiment, the proportion of the ion exchange resin in the composite membrane of the present disclosure is preferably 50% by mass to 95% by mass, more preferably 60% by mass to 94% by mass, and even more preferably 70% by mass to 93% by mass.

[0069] When a composite membrane is produced using an ion exchange resin containing fluorine atoms in its molecular structure, hydrofluoric acid may be generated due to decomposition of the ion exchange resin when the composite membrane operates as a solid polymer electrolyte membrane, etc. Therefore, the ion exchange resin is preferably an ion exchange resin that does not contain fluorine atoms in its molecular structure or has a fluorine atom content of 50 mass% or less in its molecular structure.

[0070] In the composite membrane of the present disclosure, other resins having low or no ion exchange capacity (hereinafter sometimes referred to as non-ion exchange resins) may be used in combination with the ion exchange resin. In the present disclosure, the non-ion exchange resin has an EW of 10,000 or more. Specific examples of non-ion exchange resins include resins containing structural units represented by the above general formulas (I) to (XIII).

[0071] When the composite membrane of the present disclosure uses an ion exchange resin and a non-ion exchange resin in combination, the content ratio of the ion exchange resin and the non-ion exchange resin is not particularly limited. For example, the content ratio of the ion exchange resin and the non-ion exchange resin may be adjusted so that the EW of the mixture of the ion exchange resin and the non-ion exchange resin is a desired value. In the present disclosure, "the use of an ion exchange resin and a non-ion exchange resin in combination" means that the ion exchange resin and the non-ion exchange resin are in a mutually compatible state. The non-ion exchange resin does not include the polyolefin constituting the porous substrate. The EW of the mixture of the ion exchange resin and the non-ion exchange resin is preferably 200 or more, more preferably 250 or more, even more preferably 300 or more, and particularly preferably 350 or more. The EW is preferably 2600 or less, more preferably 2300 or less, even more preferably 2000 or less, and particularly preferably 1700 or less. When the EW is 2600 or less, the ion conductivity of the composite membrane is further improved. When the EW is 200 or more, the dimensional stability of the composite membrane is further improved. The EW of the mixture of the ion exchange resin and the non-ion exchange resin is preferably 200 to 2600. In one embodiment, the mass-based content of the ion exchange resin in the mixture of the ion exchange resin and the non-ion exchange resin is preferably 1 mass% to 95 mass%, more preferably 5 mass% to 90 mass%, and even more preferably 10 mass% to 80 mass%. In one embodiment, the sulfonation rate of a mixture of an ion exchange resin and a non-ion exchange resin is preferably 5 mol % to 90 mol %, more preferably 8 mol % to 80 mol %, and even more preferably 10 mol % to 70 mol %. In the present disclosure, the sulfonation ratio for a mixture of an ion exchange resin and a non-ion exchange resin when both the ion exchange resin and the non-ion exchange resin are aromatic means the ratio of structural units substituted with sulfonic acid groups to all structural units contained in the ion exchange resin and the non-ion exchange resin. When both the ion exchange resin and the non-ion exchange resin are aromatic, the sulfonation ratio of the ion exchange resin (or the mixture of the ion exchange resin and the non-ion exchange resin when the ion exchange resin and the non-ion exchange resin are used in combination) is the value calculated from the ratio of unit structures having a sulfonic acid group to unit structures not having a sulfonic acid group, as measured by proton NMR measurement. In addition, when the types and molecular weights (e.g., weight average molecular weights) of the structural units constituting the ion exchange resin and non-ion exchange resin in the mixture and the sulfonation rate of the ion exchange resin are known, the sulfonation rate calculated based on these values ​​is regarded as the sulfonation rate for the mixture.

[0072] In addition, the durability of the ion exchange resin may decrease with an increase in the sulfonation rate. Therefore, when an ion exchange resin with a relatively low sulfonation rate is used, it is not necessary to use it in combination with a non-ion exchange resin. In addition, when an ion exchange resin with a relatively low sulfonation rate is used in combination with a non-ion exchange resin, the mass content of the ion exchange resin in the mixture of the ion exchange resin and the non-ion exchange resin may be relatively high. On the other hand, when an ion exchange resin having a relatively high sulfonation rate is used, it is preferable to use an ion exchange resin in combination with a non-ion exchange resin. For example, when a sulfonated polyethersulfone having a sulfonation rate of 1 mol % to 20 mol % (preferably 3 mol % to 18 mol %, more preferably 5 mol % to 15 mol %) is used as the ion exchange resin, the sulfonated polyethersulfone may be used alone as the ion exchange resin. On the other hand, when a sulfonated polyethersulfone having a sulfonation rate of more than 20 mol% and not more than 60 mol% (preferably 25 mol% to 50 mol%, more preferably 30 mol% to 45 mol%) is used as the ion exchange resin, the sulfonated polyethersulfone may be used in combination with a non-ion exchange resin as the ion exchange resin from the viewpoint of durability of the composite membrane. In this case, the mass-based content of the ion exchange resin in the mixture of the ion exchange resin and the non-ion exchange resin is preferably 10 mass% to 95 mass%, more preferably 20 mass% to 90 mass%, and even more preferably 25 mass% to 85 mass%.

[0073] The weight average molecular weight (Mw) of the ion exchange resin is preferably from 30,000 to 1,000,000, more preferably from 35,000 to 800,000, and even more preferably from 40,000 to 500,000, from the viewpoint of durability and mechanical properties of the composite membrane. The weight average molecular weight of the non-ion exchange resin is preferably from 30,000 to 1,000,000, more preferably from 50,000 to 800,000, and even more preferably from 80,000 to 500,000, from the viewpoint of durability of the composite membrane. The weight average molecular weight of the mixture of the ion exchange resin and the non-ion exchange resin is preferably 50,000 to 800,000, more preferably 80,000 to 650,000, and even more preferably 100,000 to 500,000, from the viewpoint of durability of the composite membrane. In the present disclosure, the weight average molecular weight of a resin refers to a value measured by gel permeation chromatography (GPC).

[0074] In the composite membrane of the present disclosure, the content of the silica material relative to the total of the silica material and the ion exchange resin (when a non-ion exchange resin is used in combination, the total amount of the ion exchange resin and the non-ion exchange resin) is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.5 mass% or more, and particularly preferably 0.7 mass% or more, from the viewpoint of improving membrane formability. In the composite membrane of the present disclosure, the content of the silica material relative to the total of the silica material and the ion exchange resin is preferably 90 mass% or less, more preferably 80 mass% or less, even more preferably 60 mass% or less, and particularly preferably 50 mass% or less, from the viewpoint of improving membrane formability. In the composite membrane of the present disclosure, the content of the silica material relative to the total of the silica material and the ion exchange resin is preferably 0.01 mass% to 90 mass%, more preferably 0.1 mass% to 80 mass%, even more preferably 0.5 mass% to 60 mass%, and particularly preferably 0.7 mass% to 50 mass%.

[0075] (Composite membrane characteristics) From the viewpoint of gas barrier properties, the Gurley value of the composite membrane is set to 1,000 seconds / 100 mL or more, preferably 2,000 seconds / 100 mL or more, and more preferably 10,000 seconds / 100 mL or more. The Gurley value of the porous substrate is a value measured in accordance with JIS P8117:2009.

[0076] From the viewpoint of increasing the strength of the composite membrane, the average thickness of the composite membrane is preferably 3 μm or more, more preferably 4 μm or more, even more preferably 5 μm or more, particularly preferably 10 μm or more, and most particularly preferably 15 μm or more. From the viewpoint of maintaining proton conductivity, the average thickness of the composite membrane is preferably 400 μm or less, more preferably 350 μm or less, even more preferably 300 μm or less, particularly preferably 150 μm or less, and even more particularly preferably 100 μm or less. The average thickness of the composite membrane is preferably 3 μm to 400 μm, more preferably 4 μm to 350 μm, further preferably 5 μm to 300 μm, particularly preferably 10 μm to 150 μm, and most particularly preferably 15 μm to 100 μm. The average thickness of the composite film is determined by measuring 20 points with a contact type film thickness meter and averaging the measurements.

[0077] From the viewpoint of dimensional stability, the ratio (A / B) of the average thickness A of the porous substrate to the average thickness B of the composite membrane is preferably 0.10 or more, more preferably 0.12 or more, even more preferably 0.13 or more, and particularly preferably 0.14 or more. From the viewpoint of proton conductivity, the ratio (A / B) is preferably 1.0 or less, more preferably 0.80 or less, further preferably 0.70 or less, and particularly preferably 0.60 or less. The ratio (A / B) is preferably from 0.10 to 1.0, more preferably from 0.12 to 0.80, further preferably from 0.13 to 0.70, and particularly preferably from 0.14 to 0.60.

[0078] The weight of the composite membrane is set at 1g / m for ease of handling. 2 More than 2g / m is preferable. 2 More preferably, 5 g / m 2 More preferably, 7 g / m 2 The above is particularly preferred. The weight of the composite membrane is set at 100g / m from the viewpoint of dimensional stability. 2 Less than 70 g / m is preferable. 2 Less than 50 g / m is more preferable. 2 More preferably, 45 g / m 2 The following are particularly preferred: The weight of the composite membrane is 1g / m 2 ~100g / m 2 is preferred, and 2 g / m 2 ~70g / m 2 More preferably, 5 g / m 2 ~50g / m 2 More preferably, 7 g / m 2 ~45g / m 2 The basis weight of the composite membrane is determined by measuring the weight of a sample of a given size and dividing the weight by the area.

[0079] From the viewpoint of dimensional stability, the ratio (C / D) of the basis weight C of the porous substrate to the basis weight D of the composite membrane is preferably 0.03 or more, more preferably 0.04 or more, even more preferably 0.05 or more, and particularly preferably 0.055 or more. From the viewpoint of proton conductivity, the ratio (C / D) is preferably 0.5 or less, more preferably 0.4 or less, further preferably 0.3 or less, and particularly preferably 0.2 or less. The ratio (C / D) is preferably from 0.03 to 0.5, more preferably from 0.04 to 0.4, further preferably from 0.05 to 0.3, and particularly preferably from 0.055 to 0.2.

[0080] (Composite membrane structure) The composite membrane of the present disclosure is not particularly limited in structure as long as it contains the above-mentioned porous substrate, silica material, and ion exchange resin. In order to ensure ion conductivity between one surface side and the other surface side of the composite membrane, it is preferable that at least a part of the pores of the porous substrate is filled with the silica material and the ion exchange resin, and it is more preferable that the entire pores of the porous substrate are filled with the silica material and the ion exchange resin.

[0081] The composite membrane of the present disclosure may have a structure including a porous substrate and an ion-conducting layer containing a silica material and an ion exchange resin provided on at least one surface side of the porous substrate. The structure of the composite membrane of the present disclosure will be described below with reference to the drawings. The drawings are schematic cross-sectional views mainly for explaining the stacking order of layers, and the structure of each layer is omitted or simplified. The size of the members in each drawing is conceptual, and the relative relationship of the size between the members is not limited thereto. The same reference numerals are given to members having substantially the same function throughout the drawings, and duplicated descriptions may be omitted. FIG 1 shows a cross-sectional view of one embodiment of the composite membrane of the present disclosure. The composite membrane 40 shown in FIG 1 has a porous substrate 20 and ion-conducting layers 30 provided on both sides of the porous substrate 20. At least a portion of the pores of the porous substrate 20 is filled with a silica material and an ion exchange resin. It is more preferable that the entire pores of the porous substrate are filled with the silica material and the ion exchange resin. Fig. 2 shows a cross-sectional view of another embodiment of the composite membrane of the present disclosure. The composite membrane 40 shown in Fig. 2 has a porous substrate 20 and an ion-conducting layer 30 provided on one side of the porous substrate 20. At least a portion of the pores of the porous substrate 20 is filled with a silica material and an ion exchange resin. It is more preferable that the entire pores of the porous substrate are filled with the silica material and the ion exchange resin. The details of the porous substrate 20 and the details of the silica material and ion exchange resin that constitute the ion conduction layer 30 are as described above.

[0082] (Method of manufacturing composite membrane) The composite membranes of the present disclosure may be made by any method. For example, a composite membrane of the present disclosure may be produced by applying a liquid composition containing an ion exchange resin, a silica material, and a solvent to a porous substrate, or by contacting a porous substrate with a coating formed from the liquid composition. The solvent contained in the liquid composition may be a solvent capable of dissolving or dispersing an ion exchange resin, and examples of such solvents include alcohols such as methanol, ethanol, n-propanol, isopropanol, and tert-butanol; diol solvents such as ethylene glycol, 1,2-propylene glycol, and 1,3-propylene glycol; aprotic solvents such as dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone; fluorine-containing alcohols; and fluorine-containing ethers. If necessary, additives such as a dispersant such as a surfactant, a wetting agent, an antifoaming agent, a pH adjuster, etc. may be added to the liquid composition. A coating film formed from a liquid composition can be obtained, for example, by applying the liquid composition onto a substrate. Examples of the substrate include plastic films such as Teflon (registered trademark), polyester, polyimide, and polycarbonate; metal films such as aluminum, copper, iron, and stainless steel; and glass. Examples of the application method of the liquid composition include a doctor knife method, a bar coater method, a spin coater method, and a screen printing method as a batch method, and a post-metering method and a pre-metering method as a continuous method. The post-metering method is a method in which an excess coating liquid is applied and then removed so as to obtain a predetermined film thickness. The pre-metering method is a method in which an amount of coating liquid required to obtain a predetermined film thickness is applied. Examples of the post-metering method include an air doctor coater method, a blade coater method, a rod coater method, a knife coater method, a squeeze coater method, an impregnation coater method, and a comma coater method, and examples of the pre-metering method include a die coater method, a reverse roll coater method, a transfer roll coater method, a gravure coater method, a kiss roll coater method, a cast coater method, a spray coater method, a curtain coater method, a calendar coater method, and an extrusion coater method. A drying treatment may be carried out to remove the solvent from the applied liquid composition. The drying is carried out, for example, in a high-temperature environment. The drying temperature is preferably 40° C. to 100° C. There is no particular limitation on the drying time, and the composite film may be dried until it becomes self-supporting.

[0083] A composite membrane of the present disclosure may be produced, for example, as follows. A liquid composition is applied to a substrate such as glass to form a coating film, then a porous substrate is laminated on the coating film, and the coating film is left to stand for a while before drying to obtain a laminate having an ion-conducting layer on one side of the porous substrate. A liquid composition is then applied to the other side of the porous substrate to form a coating film, and the coating film is left to stand for a while before drying to obtain a laminate having an ion-conducting layer on both sides of the porous substrate. The laminate is then washed with purified water such as ion-exchanged water or distilled water and dried to obtain a composite membrane. The composite membrane of the present disclosure may also be produced, for example, as follows. A liquid composition is applied onto a substrate such as glass to form a coating film, and then a porous substrate is laminated onto the coating film, and the laminate is left to stand for a while and then dried to obtain a laminate having an ion-conducting layer on one side of the porous substrate. The laminate is then washed with purified water such as ion-exchanged water or distilled water and dried to obtain a composite membrane. The drying conditions, coating conditions, washing conditions, etc. are appropriately set in consideration of the shape, film thickness, etc. of the composite film.

[0084] <Membrane / electrode assembly> The membrane-electrode assembly of the present disclosure includes the composite membrane of the present disclosure, a cathode laminated on one surface of the composite membrane, and an anode laminated on the other surface of the composite membrane. The membrane-electrode assembly of the present disclosure may have other configurations in addition to the composite membrane, the anode, and the cathode. For example, gas diffusion layers may be disposed on the surface of the cathode opposite the composite membrane and on the surface of the anode opposite the composite membrane. The membrane-electrode assembly of the present disclosure is suitably used in a polymer electrolyte fuel cell or a polymer electrolyte electrolysis device.

[0085] Examples of methods for producing a membrane electrode assembly include (1) a method in which a coating liquid containing an ion exchange resin, a catalytic metal, and a solvent is prepared, the coating liquid is directly applied to a composite membrane, the solvent contained in the coating liquid is dried and removed to form a catalytic layer, and the membrane is sandwiched between gas diffusion layers from both sides, (2) a method in which the coating liquid is applied to a substrate that will become a gas diffusion layer, the coating liquid is dried to form a catalytic layer, and the catalytic layer is then bonded to the composite membrane by a method such as hot pressing, and (3) a method in which the coating liquid is applied to a film (substrate) that is sufficiently stable against the solvent contained in the coating liquid, the coating liquid is dried to form a catalytic layer, the catalytic layer is hot pressed onto the composite membrane, the substrate film is peeled off, and the membrane is sandwiched between gas diffusion layers. The ion exchange resin contained in the coating liquid may be the same as the ion exchange resin that constitutes the composite membrane.

[0086] When the membrane-electrode assembly of the present disclosure is used in a polymer electrolyte fuel cell, the gas diffusion layer is responsible for supplying hydrogen and air as fuel to the electrode, collecting electrons generated by chemical reactions at the electrode, and keeping the composite membrane moist. As the gas diffusion layer, a conventionally known material having excellent gas permeability, acid resistance, electrical conductivity, and mechanical strength, such as carbon paper or carbon cloth, can be used. In addition, it is also preferable to dispose a microporous layer on the surface of the gas diffusion layer on the electrode side in order to promote water discharge and moisture retention from the gas diffusion layer. When the membrane-electrode assembly of the present disclosure is used in a solid polymer electrolysis device, the gas diffusion layer may be made of a conventionally known material composed of a carbon material such as carbon paper or carbon cloth, or a metal material such as stainless steel (Fe-Cr alloy, Fe-Ni-Cr alloy, etc.), aluminum, zinc, nickel, or titanium.

[0087] When the membrane-electrode assembly of the present disclosure is used in a polymer electrolyte fuel cell, the catalyst contained in the catalyst layer may be the same or different between the anode side (hydrogen electrode) and the cathode side (air electrode), but a metal catalyst made of platinum or a platinum alloy supported on carbon is preferred. The carbon support is preferably a carbon support having a specific surface area of ​​50 m2 or more, since the metal catalyst is supported on the carbon support with good dispersibility and has excellent activity of the electrode reaction stable over a long period of time. 2 / g~2000m2 It is preferred that the molecular weight is / g. The metal catalyst is preferably a metal catalyst made of platinum, since it is highly active in the hydrogen oxidation reaction at the anode and the oxygen reduction reaction at the cathode in the polymer electrolyte fuel cell. A metal catalyst made of a platinum alloy is also preferable, since it may be possible to further impart stability and activity as an electrode catalyst. The platinum alloy is preferably an alloy of platinum and one or more metals selected from the group consisting of platinum group metals other than platinum (ruthenium, rhodium, palladium, osmium, iridium), gold, silver, chromium, iron, titanium, manganese, cobalt, nickel, molybdenum, tungsten, aluminum, silicon, zinc, and tin, and the platinum alloy may contain an intermetallic compound of platinum and a metal alloyed with platinum. When a gas containing carbon monoxide is supplied to the anode, it is preferable to use an alloy containing platinum and ruthenium, since the activity of the catalyst is stabilized. When the membrane-electrode assembly of the present disclosure is used in a solid polymer electrolysis device, a metal catalyst made of platinum or a platinum alloy is preferably supported on carbon on the cathode side (hydrogen electrode), while iridium, platinum, or the like can be used as a catalyst on the anode side (air electrode).

[0088] <Solid polymer electrolyte fuel cells, solid polymer electrolyte electrolysis devices, and electrochemical hydrogen compression devices> The composite membrane of the present disclosure can be used in polymer electrolyte fuel cells, polymer electrolyte electrolysis devices, electrochemical hydrogen compression devices, and the like. In a solid polymer electrolysis device, hydrogen and the like can be produced by electrolyzing water or an organic solvent. The polymer electrolyte fuel cell and polymer electrolyte electrolysis device of the present disclosure include the membrane-electrode assembly of the present disclosure and separators disposed on both sides of the membrane-electrode assembly. A separator is disposed on the outside of the membrane-electrode assembly of the present disclosure to form a single cell. Such a single cell may be used alone, or a plurality of single cells may be stacked with a cooling plate or the like interposed therebetween to form a polymer electrolyte fuel cell or a polymer electrolyte electrolysis device. The separator serves to block fuel and air between solid polymer fuel cell stacks or solid polymer electrolysis device stacks and provides a fuel flow path, and can be made of a conventionally known carbon material or a metal material such as stainless steel. The electrochemical hydrogen compression device of the present disclosure also includes the composite membrane of the present disclosure. The electrochemical hydrogen compression device of the present disclosure may include, for example, the composite membrane of the present disclosure, a cathode provided on one side of the composite membrane, an anode provided on the other side of the composite membrane, an anode supply channel for supplying a hydrogen-containing gas to the anode, a cathode discharge channel for extracting purified hydrogen gas generated from the cathode, and a power source for applying a voltage to the anode and the cathode. EXAMPLES

[0089] The composite membrane of the present disclosure will be described in more detail below with reference to examples. The materials, amounts, ratios, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present disclosure. Therefore, the scope of the composite membrane of the present disclosure should not be interpreted as being limited by the specific examples shown below.

[0090] (Preparation of porous substrate A) 60 parts by mass of ultra-high molecular weight polyethylene with a weight average molecular weight (Mw) of 4.6 million and 60 parts by mass of polyethylene with a weight average molecular weight (Mw) of 560,000 and a density of 950 kg / m 3 A polyethylene composition was prepared by mixing the polyethylene composition with 40 parts by mass of high-density polyethylene having a molecular weight of 1.0 or more and decalin as a solvent so that the concentration of the polyethylene composition was 25% by mass, thereby preparing a polyethylene solution. The above polyethylene solution was extruded into a sheet form through a die at a temperature of 166° C., and the extrudate was then cooled in a water bath having a water temperature of 20° C. to obtain a first gel-like sheet. The first gel-like sheet was pre-dried at 30° C. for 7 minutes, then stretched 1.2 times in the longitudinal direction, and then dried at 60° C. for 5 minutes to obtain a second gel-like sheet. The amount of residual solvent in the second gel-like sheet was less than 1% by mass. Next, as the second stretching, the second gel-like sheet was stretched in the longitudinal direction at a stretching ratio of 3.5 times at a temperature of 90° C., and then stretched in the transverse direction at a stretching ratio of 9.0 times at a temperature of 125° C. Immediately after the second stretching, a heat treatment (heat setting) at 128° C. was performed. The heat-set sheet was continuously immersed in a methylene chloride bath divided into three tanks for a total of 2.5 minutes to extract the solvent from the sheet. Note that the purity of the cleaning solvent when the side where immersion starts is designated as the first tank and the side where immersion ends is designated as the third tank is (low) first tank < second tank < third tank (high). After the sheet was removed from the methylene chloride bath, the sheet was dried on a heated roll at 40°C to remove the methylene chloride. The sheet was then annealed in a heated atmosphere at 110°C. Through the above steps, a porous substrate A made of a polyolefin porous membrane was obtained. The physical properties of the obtained porous substrate A are shown in Table 1. The method for measuring each physical property will be described later.

[0091] (Preparation of porous substrate B) 12 parts by mass of ultra-high molecular weight polyethylene with a weight average molecular weight of 4.6 million and 12 parts by mass of polyethylene with a weight average molecular weight of 560,000 and a density of 950 kg / m 3 A polyethylene composition was used in which 3 parts by mass of high-density polyethylene having a molecular weight of 1.0 or less was mixed with a previously prepared mixed solvent of 72 parts by mass of liquid paraffin and 13 parts by mass of decalin so that the concentration of the polyethylene composition was 15% by mass, thereby preparing a polyethylene solution. The above polyethylene solution was extruded into a sheet form through a die at a temperature of 160°C, and the extrudate was then cooled in a water bath at 25°C. A water flow was provided on the surface of the water bath to prevent the mixed solvent released from the gelled sheet in the water bath and floating on the water surface from adhering again to the sheet, thereby obtaining a gel-like sheet. The gel-like sheet was dried at 55° C. for 10 minutes and then at 95° C. for 10 minutes to remove the decalin from the gel-like sheet. The gel-like sheet was then stretched in the longitudinal direction at a temperature of 100° C. at a magnification of 5.5 times, and then stretched in the transverse direction at a temperature of 110° C. at a magnification of 13 times, and immediately thereafter subjected to a heat treatment (heat setting) at 135° C. Next, the gel-like sheet was immersed in two separate methylene chloride baths for 30 seconds each, while extracting the liquid paraffin in the sheet. Note that the purity of the cleaning solvent when the side where immersion starts is the first tank and the side where immersion ends is the second tank is (low) first tank < (high) second tank. Thereafter, the methylene chloride was dried and removed at 45°C, and the sheet was annealed while being conveyed on a roller heated to 120°C, thereby obtaining a porous substrate B made of a polyolefin porous membrane. The physical properties of the obtained porous substrate B are shown in Table 1.

[0092] (Preparation of porous substrate C) 85 parts by mass of ultra-high molecular weight polyethylene with a weight average molecular weight (Mw) of 4.6 million and 85 parts by mass of polyethylene with a weight average molecular weight (Mw) of 560,000 and a density of 950 kg / m 3 A polyethylene composition was prepared by mixing the polyethylene composition with 15 parts by mass of high-density polyethylene having a molecular weight of 1.0 or more and 15 parts by mass of high-density polyethylene having a molecular weight of 1.0 or more. Next, the polyethylene composition was mixed with decalin as a solvent so that the concentration of the polyethylene composition was 30% by mass, thereby preparing a polyethylene solution. The above polyethylene solution was extruded into a sheet form through a die at a temperature of 158° C., and the extrudate was then cooled in a water bath having a water temperature of 20° C. to obtain a first gel-like sheet. The first gel-like sheet was pre-dried at 60° C. for 10 minutes, then stretched 1.2 times in the longitudinal direction, and then dried at 60° C. for 5 minutes to obtain a second gel-like sheet. The amount of residual solvent in the second gel-like sheet was less than 1% by mass. Next, as the second stretching, the second gel-like sheet was stretched in the longitudinal direction at a stretching ratio of 4.5 times at a temperature of 90° C., and then stretched in the transverse direction at a stretching ratio of 10.0 times at a temperature of 125° C. Immediately after the second stretching, a heat treatment (heat setting) at 134° C. was performed. The heat-fixed sheet was continuously immersed in a methylene chloride bath divided into three tanks for a total of 2.5 minutes to extract the solvent from the sheet. Note that the purity of the cleaning solvent when the side where immersion starts is designated as the first tank and the side where immersion ends is designated as the third tank is (low) first tank < second tank < third tank (high). After the sheet was removed from the methylene chloride bath, the sheet was dried on a heated roll at 40°C to remove the methylene chloride. The sheet was then annealed in a heated atmosphere at 80°C. Through the above steps, a porous substrate C made of a polyolefin porous membrane was obtained. The physical properties of the obtained porous substrate C are shown in Table 1.

[0093] - Weight average molecular weight of polyethylene - The weight average molecular weight of the polyethylene was measured by gel permeation chromatography. Specifically, the polyethylene to be measured was dissolved by heating in o-dichlorobenzene, and the measurement was performed by gel permeation chromatography (system: Alliance GPC 2000 manufactured by Waters, columns: GMH6-HT and GMH6-HTL) under conditions of a column temperature of 135°C and a flow rate of 1.0 mL / min. Molecular weight monodisperse polystyrene (manufactured by Tosoh Corporation) was used for molecular weight calibration.

[0094] (Characteristics of porous substrate) The properties of the porous substrate were measured by the following methods. -Average thickness of porous substrate A- The average film thickness A of the porous substrate was measured using a contact type film thickness meter (Mitutoyo Corporation, ABS Digimatic Indicator, Model ID: ID-S112X). Specifically, the film thickness of the porous substrate was measured at 20 points, and the arithmetic average value was taken as the average film thickness A of the porous substrate. A cylindrical terminal with a bottom diameter of 6.5 mm was used as the contact terminal.

[0095] -Weight of porous substrate C- The porous substrate was cut to prepare a sample of 10 cm × 10 cm. The basis weight C of the porous substrate was determined by multiplying the measured mass of the sample by 100.

[0096] -Porosity of porous substrate- The porosity (ε) of the porous substrate was calculated by the following formula. ε(%)={1-Ws / (ds·t)}×100 Ws: Weight of porous substrate (g / m 2 ) ds: True density of polyolefin (g / cm 3 ) t: membrane thickness of porous substrate (μm) The basis weight of the porous substrate was determined by the method described above.

[0097] -Air permeability of porous substrate (Gurley value)- The Gurley value of the porous substrate was measured using a Gurley densometer manufactured by Toyo Seiki Co., Ltd. in accordance with JIS P8117: 2009. The time it took for 200 ml of air to pass through a 28.6 mm diameter sample was measured, and the time was halved to convert it to a value per 100 ml.

[0098] -Average pore size of porous substrate- The average pore size of the porous substrate was measured by the half-dry method specified in ASTM E1294-89 using a PMI Palm Porometer (model: CFP-1200-AEXL) and PMI Galwick (surface tension 15.9 dyn / cm) as the immersion liquid. The measurement temperature was 25°C, and the measurement pressure was changed in the range from 0 kPa to 600 kPa.

[0099] [Table 1]

[0100] (Manufacturing of Silica Materials) 10 parts by mass of silicon dioxide (Sigma-Aldrich, number average particle size of primary particles: 10 nm to 20 nm, silica particles) was gradually added to 400 parts by mass of concentrated sulfuric acid (concentration: 99.9%) at 25°C, and treated at 1500 rpm for 15 minutes using a SpeedMixer DAC400 manufactured by Hauschild to obtain a dispersion liquid in which silica particles were dispersed in concentrated sulfuric acid. The obtained dispersion liquid was gradually added to 4000 parts by mass of deionized water, washed, and then filtered to recover the silica particles obtained as a residue. The recovered silica particles were further washed with 4000 parts by mass of deionized water, filtered, and the residue was recovered. The obtained residue was washed with 200 parts by mass of acetone and filtered again. The residue was dried in a hot air dryer at 80°C to obtain 14.5 parts by mass of a particulate silica material. The degree of sulfonation of this silica material based on XRF was 0.3% when measured by the method described below. The pH of this dispersion of silica material was measured by the method described below and was found to be 1.2.

[0101] -pH measurement- 0.1 g of the silica material was dispersed in 1.9 g of deionized water to prepare a dispersion (5 mass% dispersion). The pH of the dispersion was measured at 25°C using a pH meter (PCE-PH18).

[0102] -Measurement of sulfonation degree- The silica material was weighed out in a measurement container under a helium atmosphere and measured using an XRF measurement device (PANalytical AxiosMAX). The concentrations of sulfur atoms and silicon atoms were calculated from the obtained spectrum, and the ratio of the sulfur atom concentration to the total concentration of silicon atoms and sulfur atoms was taken as the degree of sulfonation. In addition, SEM-EDX measurement confirmed that the silica material had sulfonic acid groups on its surface. -Measurement of the number-average particle size of primary particles- The number-average particle size of the primary particles of the silica particles was calculated as the arithmetic mean value of the circle-equivalent diameters of 50 silica particles determined by observation with a scanning electron microscope.

[0103] (Preparation of Liquid Composition 1) The above-mentioned silica material was added to N,N-dimethylacetamide (DMAc) and dispersed in an ultrasonic bath until uniform, to obtain a silica material dispersion. Next, sulfonated polyethersulfone (s-PES, EW: 500g / eq, weight average molecular weight: 140000, acts as an ion exchange resin) with a sulfonation rate of 34.1 mol% was added while stirring the silica material dispersion, to obtain a liquid composition 1 with a solid concentration of 10 mass% and a silica material content of 1 mass% in the solid content. The weight average molecular weight of the s-PES was determined according to the following method. Device name: High-performance liquid chromatograph LC-20A series (Shimadzu Corporation) Column oven: CTO-20A Mobile phase: N-methyl-2-pyrrolidone Autosampler: SIL-20AHT LC workstation:LC solution Flow rate: 0.3ml / min Differential refractometer detector: RID-10A Oven temperature: 60℃ Molecular weight standards: Polystyrene

[0104] (Preparation of Liquid Composition 2) Liquid composition 2 was obtained in the same manner as in the preparation of liquid composition 1, except that the solid concentration was 10% by mass and the content of the silica material in the solids was 2% by mass.

[0105] (Preparation of Liquid Composition 3) Liquid composition 3 was obtained in the same manner as in the preparation of liquid composition 1, except that the solid concentration was 10% by mass and the content of the silica material in the solids was 5% by mass.

[0106] (Preparation of Liquid Composition 4) Liquid composition 4 was obtained in the same manner as in the preparation of liquid composition 1, except that the solid concentration was 10% by mass and the content of the silica material in the solids was 10% by mass.

[0107] (Preparation of Liquid Composition 5) By adding sulfonated polyethersulfone (s-PES, EW: 500 g / eq, weight average molecular weight: 140,000) with a sulfonation rate of 34.1 mol% while stirring N,N-dimethylacetamide (DMAc), a liquid composition 5 having a solid concentration of 10 mass% and a silica material content of 0 mass% in the solid content was obtained.

[0108] [Example 1] Liquid composition 1 was cast onto a glass plate using a doctor knife (200 μm), and porous substrate A was laminated on the cast liquid composition 1 without wrinkles. After standing for 10 minutes, it was dried for 30 minutes in a hot air dryer at 60°C. Liquid composition 1 was cast onto the laminate obtained by drying using a doctor knife (200 μm), and then it was left to stand for 10 minutes. After drying for 30 minutes in a hot air dryer at 60°C, it was washed with ion-exchanged water for 10 minutes. It was further fixed to a metal frame and dried for 10 minutes at 60°C to obtain composite membrane 1.

[0109] [Example 2] A composite membrane 2 was obtained in the same manner as in Example 1, except that liquid composition 2 was used instead of liquid composition 1.

[0110] [Example 3] A composite membrane 3 was obtained in the same manner as in Example 1, except that Liquid composition 3 was used instead of Liquid composition 1.

[0111] [Example 4] A composite membrane 4 was obtained in the same manner as in Example 1, except that Liquid composition 4 was used instead of Liquid composition 1.

[0112] [Example 5] The liquid composition 3 was cast onto a glass plate using a doctor knife (100 μm), and the porous substrate B was laminated on the cast liquid composition 3 without wrinkles. After being left to stand for 10 minutes, it was dried for 30 minutes in a hot air dryer at 60°C. The liquid composition 3 was cast onto the laminate obtained by drying using a doctor knife (100 μm), and then it was left to stand for 10 minutes. After being dried for 30 minutes in a hot air dryer at 60°C, it was washed with ion-exchanged water for 10 minutes. It was further fixed to a metal frame and dried for 10 minutes at 60°C to obtain a composite membrane 5.

[0113] [Example 6] A composite membrane 6 was obtained in the same manner as in Example 5, except that liquid composition 4 was used instead of liquid composition 3.

[0114] [Example 7] A composite membrane 7 was obtained in the same manner as in Example 3, except that the porous substrate C was used instead of the porous substrate A.

[0115] [Reference example 1] Liquid composition 1 was cast onto a glass plate using a doctor knife (200 μm), and the cast liquid composition 1 was left to stand for 10 minutes, and then dried for 30 minutes in a hot air dryer at 60° C. Liquid composition 1 was cast again onto the resin film obtained by drying using a doctor knife (200 μm), and then left to stand for 10 minutes. After drying for 30 minutes in a hot air dryer at 60° C., the film was washed with ion-exchanged water for 10 minutes. The film was then fixed to a metal frame and dried for 10 minutes at 60° C. to obtain a reference resin film 1.

[0116] [Reference example 2] A reference resin film 2 was obtained in the same manner as in Reference Example 1, except that Liquid Composition 3 was used instead of Liquid Composition 1.

[0117] [Reference example 3] The liquid composition 3 was cast onto a glass plate using a doctor knife (200 μm) and dried for 30 minutes in a hot air dryer at 60° C. The plate was washed with ion-exchanged water for 10 minutes and then dried for 10 minutes at 60° C. to obtain a reference resin film 3.

[0118] [Reference example 4] A reference resin film 4 was obtained in the same manner as in Reference Example 1, except that Liquid Composition 4 was used instead of Liquid Composition 1.

[0119] [Comparative Example 1] The liquid composition 5 was cast onto a glass plate using a doctor knife (200 μm), and the porous substrate A was laminated on the cast liquid composition 5 without wrinkles. After leaving it to stand for 10 minutes, it was dried for 30 minutes in a hot air dryer at 60°C. The liquid composition 5 was cast onto the laminate obtained by drying using a doctor knife (200 μm), and then left to stand for 10 minutes. After drying for 30 minutes in a hot air dryer at 60°C, it was washed with ion-exchanged water for 10 minutes. It was further fixed to a metal frame and dried for 10 minutes at 60°C to obtain a comparative composite membrane 1.

[0120] [Comparative Example 2] The liquid composition 5 was cast onto a glass plate using a doctor knife (100 μm), and the porous substrate B was laminated on the cast liquid composition 5 without wrinkles. After leaving it to stand for 10 minutes, it was dried for 10 minutes in a hot air dryer at 60° C. The liquid composition 5 was cast onto the laminate obtained by drying using a doctor knife (100 μm), and then left to stand for 10 minutes. After drying for 30 minutes in a hot air dryer at 60° C., it was washed with ion-exchanged water for 10 minutes. It was further fixed to a metal frame and dried for 10 minutes at 60° C. to obtain a comparative composite membrane 2.

[0121] [Comparative Example 3] Liquid composition 5 was cast onto a glass plate using a doctor knife (200 μm), and the cast liquid composition 5 was left to stand for 10 minutes, and then dried for 30 minutes in a hot air dryer at 60° C. Liquid composition 5 was cast again onto the resin film obtained by drying using a doctor knife (200 μm), and then left to stand for 10 minutes. After drying for 30 minutes in a hot air dryer at 60° C., the film was washed with ion-exchanged water for 10 minutes. The film was then fixed to a metal frame and dried for 10 minutes at 60° C. to obtain a comparative resin film 3.

[0122] (evaluation) The composite membranes and resin membranes of the Examples, Reference Examples, and Comparative Examples obtained as described above were evaluated by the following methods. The results are shown in Table 2. -Composite membrane weight D and resin membrane weight- The basis weight D of the composite membrane and the basis weight of the resin membrane were determined in the same manner as in the above-mentioned "basis weight C of the porous substrate." -Average thickness of composite film B and average thickness of resin film- The average thickness B of the composite membrane and the average thickness of the resin membrane were determined in the same manner as in the "average thickness A of the porous substrate" described above.

[0123] -Amount of adhesion- From the basis weight C of the porous substrate and the basis weight D of the composite membrane determined as described above, the adhesion amounts of the silica material and the ion exchange resin to the porous substrate were calculated. Adhesion amount (g / m 2 ) = Composite membrane basis weight D (g / m 2 )-Weight of porous substrate C(g / m 2 )

[0124] -Air permeability of composite membrane and resin membrane (Gurley value)- The Gurley values ​​of the composite membrane and the resin membrane were determined in the same manner as in the above-mentioned "Air permeability (Gurley value) of the porous substrate." In Table 2, "∞" means that the Gurley value is 10,000 seconds / 100 mL or more.

[0125] -Content of each component (mass%)- The contents (mass%) of s-PES, porous substrate and silica material (sSiO2) in the entire composite membrane were calculated based on the amounts of the silica material and ion exchange resin attached to the porous substrate, the proportions of the s-PES and silica material in the solid content contained in the liquid composition, and the basis weights of the composite membrane and porous substrate.

[0126] -Proton conductivity- The proton conductivity of the composite membrane and the resin membrane was measured by the following method. Using an electrochemical impedance measuring device (TSC Battery manufactured by rhd instruments), impedance measurement was performed in the thickness direction of the composite membrane or resin membrane in the frequency range of 50Hz to 107Hz, and proton conductivity was measured and used as an index of proton conductivity. Each composite membrane and resin membrane used in the above measurement was stored in deionized water, and was heated to 80°C in a measurement cell before being subjected to the measurement of proton conductivity.

[0127] - Area change rate - The composite film and the resin film were dried in a dryer at 50°C until there was no weight change. After that, the lengths of the composite film and the resin film in the longitudinal and width directions were measured (condition 1). The linear distances connecting the centers of the opposing sides were defined as the longitudinal and width directions. The composite membrane and the resin membrane were kept in pure water for 64 hours, and then subjected to hot water treatment at 80° C. for 2 hours, and the lengths in the longitudinal and transverse directions were immediately measured (condition 2). The dimensional change rate was determined using the above measurement results, and the area was calculated by calculating the length in the longitudinal direction x the length in the transverse direction, and the area change rate was calculated as follows. Area change rate A = [area (condition 2) - area (condition 1)] x 100 / area (condition 2)

[0128] -The ratio of the average thickness A of the porous substrate to the average thickness B of the composite membrane (A / B)- From the average thickness A of the porous substrate and the average thickness B of the composite membrane obtained as described above, the ratio (A / B) of the average thickness A of the porous substrate to the average thickness B of the composite membrane was calculated. -The ratio of the basis weight C of the porous substrate to the basis weight D of the composite membrane (C / D)- From the basis weight C of the porous substrate and the basis weight D of the composite membrane determined as described above, the ratio (C / D) of the basis weight C of the porous substrate to the basis weight D of the composite membrane was calculated.

[0129] [Table 2]

[0130] As is clear from the evaluation results in Table 2, the composite membranes of the Examples are superior in proton conductivity and dimensional stability to the composite membranes or resin membranes of the Comparative Examples. In addition, as shown in Table 2, the proton conductivity was measured for the composite membranes of Examples 1-7 and Comparative Examples 1-2, which indicates that a proton conductive path was established between one surface and the other surface of these composite membranes. This suggests that at least a portion of the inside of the pores of the porous substrate is filled with a silica material and an ion exchange resin, and the composite membrane of the present invention is provided with an ion conductive layer. [Explanation of symbols]

[0131] 20 Porous substrate 30 Ion Conducting Layer 40 Composite membrane

Claims

1. A porous substrate comprising a polyolefin microporous membrane; A silica material having a substrate containing silicon dioxide and having sulfonic acid groups on at least a surface of the substrate; An ion exchange resin, A composite membrane having a Gurley value of 1,000 seconds / 100 mL or more.

2. 2. The composite membrane according to claim 1, wherein the porosity of the porous substrate is from 50% to 90%.

3. 2. The composite membrane according to claim 1, wherein the pores of the porous substrate are at least partially filled with the silica material and the ion exchange resin.

4. The composite membrane according to claim 1 , comprising: the porous substrate; and an ion-conducting layer, the ion-conducting layer including the silica material and the ion exchange resin, provided on at least one surface side of the porous substrate.

5. 2. The composite membrane according to claim 1, wherein the ratio (A / B) of the average thickness A of the porous substrate to the average thickness B of the composite membrane is 0.10 to 1.

0.

6. The composite membrane according to claim 1, wherein the ratio (C / D) of the basis weight C of the porous substrate to the basis weight D of the composite membrane is 0.03 to 0.

5.

7. 2. The composite membrane according to claim 1, wherein the ratio of the concentration of sulfur atoms to the total concentration of silicon atoms and sulfur atoms of the silica material, as determined by X-ray fluorescence spectroscopy (XRF), is 0.01% to 90%.

8. 2. The composite membrane of claim 1, wherein the substrate is in particulate form.

9. 2. The composite membrane according to claim 1, wherein the substrate is silica particles, and the number average particle size of the primary particles of the silica particles is 1 nm to 500 nm.

10. A membrane-electrode assembly comprising: the composite membrane according to any one of claims 1 to 9; a cathode laminated on one surface of the composite membrane; and an anode laminated on the other surface of the composite membrane.

11. A polymer electrolyte fuel cell comprising the membrane-electrode assembly according to claim 10 and separators disposed on both sides of the membrane-electrode assembly.

12. A solid polymer electrolysis device comprising the membrane-electrode assembly according to claim 10 and separators disposed on both sides of the membrane-electrode assembly.

13. An electrochemical hydrogen compression device comprising the composite membrane according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Electrolytic thin film

    JP1989022932A

  • Thin membrane electrolyte

    JP1989158051A

  • Polymer electrolyte composite membrane, its manufacturing method and solid polymer type fuel cell using it

    JP2005166557A

  • Polyethylene microporous film

    JP2011241361A